Prove that

cos(-A+B+C) + cos(A-B+C) + cos(A+B-C) + cos(A+B+C) = 4cosAcosBcosC

Similar Questions
  1. If A + B + C = 180° prove thatcos2A + cos2B – cos2C = -1 -4cosAcosBcosC
    1. answers icon 0 answers
  2. If sin a + sinb + sinc = 4cosa/2cosb/2cosc/2Then sin 2a + sin2b + sin 2c = 4cosacosbcosc
    1. answers icon 1 answer
  3. HII WOULD LIKE TO KNOW WHAT I CAN POSSIBLY PROVE ABOUT EITHER THE BERMUDA TRIANGLE OR ATLANTIS THE LOST EMPIRE WE AARE SUPPOSED
    1. answers icon 4 answers
    1. answers icon 0 answers
more similar questions